Novel Drug Targets Based on Association between Inflammation and Pancreatic Ductal Adenocarcinoma - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Yale University School of Medicine. New Haven, CT, USA.